A Consistent Hybrid LES-RANS PDF Method for Non-premixed Flames. (2015) - Ferraro, Federica; Ge, Yipeng; Pfitzner, Michael
Abstract: The computational demanding LES methods have widely demonstrated their reliability in the description of large scale unsteady phenomena in turbulent reactive flows. RANS Transported Probability Density Function (TPDF) methods treat the nonlinear chemical reactions in closed form on relatively coarse grids and using a smaller number of stochastic particles. Combining the two approaches, a hybrid LES-RANS PDF method to predict non-premixed turbulent flames is presented. In this method a LES, based on Smagorinsky's model and steady flamelet, is performed; subsequently, the calculated flow-field is used to drive the RANS-TPDF equation, which is closed at the joint scalar level and based on a Lagrangian Monte Carlo scheme. The required velocity and turbulent quantities for RANS simulation are estimated from the resolved LES and an algebraic model based on dimensional analysis and the mixing length hypothesis. The results of the velocity, turbulent kinetic energy and mixture fraction show that the consistency of the method is achieved.